Postcritical Sensibilities for the Study of the COVID-19 Pandemic - Kelly Diaz; Adetobi Moses; Jing Wang; Guobin Yang (Media Theory, 2023)
Postcritique is the name given to a recent intellectual trend which opposes the practices of suspicion and theoretical abstraction in literary and cultural studies. Its proponents champion the alternative dispositions and epistemologies of attachment, hopefulness, and care (Anker & Felski, 2017; Felski, 2015). Embedded in a longer and broader intellectual current encompassing the humanities and social sciences, postcritique crystallizes a set of critical sensibilities particularly compelling for our contemporary historical conjuncture. We delineate these sensibilities by examining works on postcritique in literary and cultural studies, briefly discuss critical expressions of such sensibilities in the 1960s and 1970s, and link them to related work in the social sciences. We then present three vignettes from our research on the COVID-19 pandemic to illustrate how an ethos of openness, hopefulness, and vulnerability may inform the study of the catastrophic experiences of an ongoing global pandemic. The three vignettes highlight the importance of documenting and understanding emotional experiences through digital media such as mobile-phone photography, audio diaries, and podcasting.